Lactate dehydrogenase as a biomarker for silica exposure-induced toxicity in agate workers - Aggarwal, Bhagwan Das (Occupational and environmental medicine (London, England), 2014)
Objectives Agate workers are chronically exposed to silica dust generated from agate grinding, which makes them susceptible to silicosis. In the absence of diagnosis at an early stage, the workers continue to be exposed to silica dust until the development of silicosis. The present study was undertaken to investigate total lactate dehydrogenase (LDH) activity in blood samples of silica-exposed agate workers as a non-invasive way to measure silica-induced toxicity. Methods Blood samples were collected from agate workers and control subjects. Total LDH activity was measured in the blood plasma and blood cells of agate workers and non-exposed (control) subjects using sodium pyruvate as a substrate. The reduction of pyruvate to L-lactate with the concurrent oxidation of nicotinamide adenine dinucleotide (NADH) during the assay was monitored by change in absorbance (or optical density (OD)) at 340 nm at the fixed interval of 10 min. The ratio of LDH activity (blood plasma/blood cells) in the blood samples was calculated as a measure to detect cytotoxicity in exposed workers. Results The LDH activity in blood plasma samples of exposed workers was found to increase about 25 times, while the activity in the blood cells of silica-exposed agate workers was reduced to 10% of control subjects. The ratio of LDH activity (blood plasma/cells) was found to be 6.6 in the silica-exposed agate workers, while it was 0.02 in control (non-exposed) subjects. Conclusions This study proposes that total LDH activity and the LDH ratio (plasma/cells), along with occupational exposure history, are markers for silica exposure-induced toxicity in agate workers.